Nematodes associated with East African Highland cooking bananas and cv. Pisang Awak (Musa spp.) in Central Uganda - Speijer, P.; Waele, D. de (Brill, 2001)
A survey was conducted at 17 sites in Central Uganda. Suckers were detached from East African Highland cooking bananas (Musa spp., AAA-group) and the cultivar Pisang Awak (Musa spp., ABB-group), and assessed for nematode population densities and root damage. The frequency of occurrence on both Musa groups was Helicotylenchus multicinctus 88%, Radopholus similis 74% and Pratylenchus goodeyi 50%. Helicotylenchus multicinctus and R. similis densities were higher (P ≤ 0.05) on Highland cooking bananas compared to Pisang Awak, while P. goodeyi densities did not differ significantly between the groups. Helicotylenchus multicinctus and R. similis were observed to be the major pests of Highland cooking bananas in Central Uganda, causing extensive root death. Radopholus similis may be the more important of the two, as it was also highly associated with root necrosis.